Factors Contributing to the Unemployment of Diploma Holders in Civil Engineering - A Study - Mittal, L. N.; Singla, P. K.; Gupta, S. K. (Journal of Engineering Education Transformations, 1996)
Diploma course in civil engineering is being offered by majority of polytechnics in the country. Considerable amount of unemployment is being experienced in the diploma holders graduating in this course. It is indeed a strange dichotomy that in a country like India, where more than 60 percent of plan budget go to construction industry directly or indirectly, diploma holders in civil engineering still face such an unemployment. This paper highlights the finding of a study conducted to ascertain the factors contributing to the unemployment of such diploma holders and make recommendations/suggestions for enhanced employability of diploma holders in this field.